Lopping in the Kumaun Himalaya of United Provinces - Drummond, R. O. (Indian Forester, 1944)
The article comprises a note on the history of lopping in the forests of Kumaun (mainly of oaks) and the influence at varying governmental policies towards lopping, It contains an appreciation of the present position; the serious "results of unrestricted lopping and the dangers inherent in the practice, unless carefully . Limited. The importance of kharaks (steadings for cattle inside forests) as centres of lopping damage is stressed, and changes in the present policy are suggested.